Polymerization of Ethylene Catalyzed by Vanadium(III) Complexes - Hamdi Ali Elagab (Orbital: The Electronic Journal of Chemistry, 2017)
Thirty five  complexes of 1,2- bis(benzimidazole, benzothiazole and benzoxazole)benzene,  1,2-bis(benzimidazole, benzothiazole and benzoxazole)-4-methyl-benzene, 1,2-bis  (benzimidazole, benzothiazole and benzoxazole)4-bromobenzene, 1, 2-bis(benzimidazole, benzothiazole and benzoxazole) 4- chlorobenzene,  and 2, 6-bis(benzimidazole, benzothiazole and benzoxazole) pyridine compounds with V (III) metal centers were synthesized, characterized, activated with methylalumoxane (MAO) and then tested for catalytic ethylene polymerization. The catalysts generally show moderate to good activities compared to the benchmark catalyst Cp2ZrCl2. The activities of the various catalysts were found to be function of the hetero atoms in the ligand frameworks and also strongly influenced by the bridging unit of the ligand. The highest activity was obtained with 36 / MAO (442 kg PE / mol cat. h). The produced polyethylenes showed high molecular weights (up to 2.7 × 106 g/mol) and broad molecular weight distributions (PD = 1.4 - 16.6). Thermal analysis of polyethylenes produced with vanadium complexes revealed that the catalyst systems were capable to produce high density polyethylenes with melting temperatures > 135 °C and crystallization temperatures range from 117-120 °C with high degree of crystallinity.DOI: http://dx.doi.org/10.17807/orbital.v9i3.985